Internet Peculiarity and Territorial Traditionalism Converge on Cyberspace: A Study of Techno-legal Synchronization in the USA - Hoque, Kazi Arshadul; Rahman, Mohammad Mahabubur (IIUC Studies, 2012)
Law is enacted and imposed by sovereign state authority. As the states are territorial in nature, the enforcement of law depends to a large extend on the ability to exercise physical control over the territory. Cyberspace and internet have no territorial-based boundaries and are almost entirely independent of physical location. In spite of inevitability of a distinct set of laws and legal principles to be adopted for cyber offences the traditional territorial law can supply element for cyber legal issues. The hi-tech pioneer American courts whether federal or provincial are very much inclined to decide the internet- cases on the basis of territorial concept by applying the principles of traditional territorial notions. This article concentrates on the study of the American cases as a representative type of hi-tech nations for searching the influences of traditional territorial concept on the settlement of internet- cases and the way for overcoming the problems came out of cyber peculiarity. This article will show how law together with internet has created a new environment in legal arena; and how the USA as high-tech nation relying upon previous territorial experience is making new pathway for the jurists, courts and all others. This article is based on keen observation and intensive analysis of American practice. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12264 IIUC Studies Vol.7 2011: 117-130